PROBLEMATIKA KEPALA SEKOLAH DALAM MENINGKATKAN MUTU MANAJEMEN PENDIDIKAN DI SEKOLAH MENENGAH: (Studi Kasus Pada Pembelajaran PPKn di SMP Negeri 1 Banjar Pandeglang) - Islamiah, Ayu Solehah (Academy of Education Journal, 2023)
This study aims to determine the information and provide solutions to the problems faced by the principal of SMP Satap Sayar Serang, especially in the management or management of Education. In this study using descriptive qualitative research methods in which the technique of collecting data through observation, interviews and documentation. The data analysis technique is done by using data reduction by determining the main things and focusing on problems or problems that exist in schools, so that from this it can provide a more focused and actual enlightenment in accordance with existing conditions to be found solutions of what causes the problems of principals in improving the quality of Education Management. Based on the results of the study showed that the problems that occur in schools are caused by human resources that are still not optimal as seen from educators and education, low public trust in schools, educational and educator performance that needs to be improved and improved together, facilities that do not have and there are still many teachers who are still honorary status and lack of supervision from the local education office in monitoring developments in schools.